Measurement of (γ, p) reactions with ∆E − E telescope at Max-lab facility - Burdeinyi, D.; Brudvik, J.; Ganenko, V.; Hansen, K.; Fissum, K.; Isaksson, L.; Livingston, K.; Lundin, M.; Nilsson, B.; Schroder, B. (Вопросы атомной науки и техники, 2015)
The paper considers the results of experiments on the reactions ¹²C(γ, p)¹¹B and d(γ, p)n in the energy range of tagged photons 35...80 MeV. Demonstrated the possibility identification of protons by ΔE - E using CsI/SSD telescope. Using the spectra of the missing energy defined the values of differential cross sections of these reactions in the range of photon energies. The good agreement of the experimental results with the available data in the literature. Розглянуто результати експериментів з вивчення реакцій ¹²C(γ, p)¹¹B і d(γ, p)n в області енергій мічених фотонів 35…80 МеВ. Показана можливість ідентифікації протонів методом ΔE-E за допомогою CsI/SSD-телескопа. Використовуючи спектри недостатніх енергій, визначені диференційні перерізи розглянутих реакцій в зазначених діапазонах енергій фотонів. Отримані експериментальні результати добре узгоджуються з літературними даними. Рассматриваются результаты экспериментов по изучению реакций ¹²C(γ, p)¹¹B и d(γ, p)n в области энергий меченых фотонов 35…80 МэВ. Показана возможность идентификации протонов методом ΔE-E с помощью CsI/SSD-телескопа. Используя спектры недостающих энергий, определены значения дифференциальных сечений рассматриваемых реакций в указанных диапазонах энергий фотонов. Показано хорошее согласие результатов экспериментов с имеющимися литературными данными.